The Economics of International Sports Events. - LI, ShiNa. (Contemporary Cases Online Series, 2013)
This case study is part of the Contemporary Cases Online series. The series provides critical case studies that are original, flexible, challenging, controversial and research-informed, driven by the needs of teaching and learning.